Partisipasi Politik Pemilih Muda Dalam Pelaksanaan Demokrasi di Pemilu 2024 - Setiawan, Heru Dian; Djafar, TB. Massa (Universitas Nasional, 2023)
In the 2024 Election, Gen Z and Gen Y will be the group of young voters who will account for 53-55% of the total number of voters. In the last two periods, the increase in participation of young voters suggests that they are being recruited just to get votes. On the other hand, there is also the impression that the increase in the number of young voters is accompanied by political awareness which can be interpreted as the level of concern that young voters still maintain regarding the current government or political system. This research aims to determine the participation of young voters in welcoming the 2024 Elections, especially the context of voting behavior. Based on research results, young voters' participation in elections can still be interpreted as a form of political awareness or the level of trust young voters maintain in the current government or political system. Today's young voters are also more rational and critical about Indonesia's future leaders. The ability of young voters to adapt to modernization requires leaders who can adapt to their generation.Pada Pemilu 2024, Gen Z dan Gen Y akan menjadi kelompok pemilih muda yang jumlahnya mencapai 53-55% dari total jumlah pemilih. Dalam dua periode terakhir, peningkatan partisipasi pemilih muda mengesankan bahwaa mereka dirangkul hanya untuk mendapatkan suara. Di sisi lain, ada pula kesan bahwa peningkatan jumlah pemilih muda diikuti oleh kesadaran politik yang bisa dimaknai sebagai masih terjaganya tingkat kepedulian pemilih muda terhadap pemerintahan atau sistem politik yang sedang berlangsung. Penelitian ini bertujuan untuk mengetahui partisipasi pemilih muda dalam menyambut Pemilu 2024 terutama konteks perilaku pemilih. Berdasarkan hasil penelitian, partisipasi pemilih muda dalam Pemilu tetap dapat dimaknai sebagai bentuk kesadaran politik atau masih terjaganya tingkat kepercayaan pemilih muda terhadap pemerintahan atau sistem politik yang sedang berlangsung. Pemilih muda saat ini juga lebih rasional dan kritis tentang pemimpin masa depan Indonesia. Kemampuan pemilih muda untuk beradaptasi dengan modernisasi membutuhkan pemimpin yang dapat menyesuaikan dengan generasinya.